Oral Care of Hospitalised Older Patients in the Acute Medical Setting - Kathryn Salamone; Elaine Yacoub; Anne-Marie Mahoney; Karen-leigh Edward (Nursing Research and Practice)
Oral health care is an essential aspect of nursing care. There are many variances in the quality and frequency of the oral care that is delivered to patients by nursing staff, such as oral care being given a low priority when compared to other nursing care elements, oral care being neglected, and oral care delivery being dependent on the nurse’s knowledge of oral hygiene. Additionally, there are some particular patient groups known to be at risk of oral health problems or who have existing oral diseases and conditions. As people age their susceptibility increases to chronic and life-threatening diseases, and they can be at increased risk of acute infections increases compromised by ageing immune systems. The aim of this literature review was to ignite the discussion related to the oral care practices of nurses for older acute medical hospitalised patients. The review revealed that nursing staff know that good nursing includes oral health care, but this knowledge does not always mean that oral health care is administered. Oral health care seems to be separated from other nursing activities and is not discussed when nursing care plans are written, only when oral problems are obvious.